Spinal Anesthesia Is Associated With Decreased Complications After Total Knee and Hip Arthroplasty. Issue 5 (1st March 2020) - Warren, Jared; Sundaram, Kavin; Anis, Hiba; Kamath, Atul F.; Mont, Michael A.; Higuera, Carlos A.; Piuzzi, Nicolas S.
Abstract : Background: We compared the following 30-day outcomes for total knee arthroplasty (TKA) and total hip arthroplasty in spinal anesthesia (SA) versus general anesthesia (GA) (1) mortality, (2) major and minor complication rates, and (3) discharge disposition. Methods: From 2011 to 2016, the American College of Surgeons National Surgical Quality Improvement Program database contained 45, 871 SA total hip arthroplasties and 65, 092 receiving GA. There were 80, 077 SA TKAs and 103, 003 GA TKAs. Adjusted multivariate logistic regression evaluated associations between anesthesia type and 30-day outcomes. Results: Anesthesia modality was not associated with 30-day mortality ( P > 0.05). The GA cohorts were at a greater risk for any complication, major complications, and minor complications ( P < 0.05). Patients who received GA were at an increased risk for nonhome discharge. Conclusion: Patients who undergo total joint arthroplasty with SA experience fewer 30-day complications and are less likely to have a nonhome discharge than those with GA.